Two new species of parasitic nematodes from the dogtooth tuna Gymnosarda unicolor (Pisces) off the Maldive Islands - Moravec, Frantisek; Lorber, Julia; Konecný, Robert (The Journal of parasitology, 2007)
Two new nematode species, Philometra gymnosardae n. sp. (Philometridae) and Heptochona maldivensis n. sp. (Rhabdochonidae), are described from the dogtooth tuna Gymnosarda unicolor (Rüppell) (Scombridae, Perciformes) from the Indian Ocean off the Maldive Islands (Republic of Maldives). The former species is characterized mainly by unequal, conspicuously long (859 and 435 microm) spicules; the structure of the caudal end in the male (found in the host's stomach); by markedly large, oval cephalic papillae (n = 8) of the outer circle; the presence of a small, anterior bulb on the very long esophagus; and 2 large caudal projections in the gravid female (parasitic in the host's body cavity). This is the first-known species of Philometra whose gravid females are present in the body cavity of tuna fishes. Heptochona maldivensis resembles H. stromatei but differs mainly in the position of deirids, shape of the muscular esophagus, character of postanal papillae, length of the left spicule (648 microm), much larger body measurements, location in the host (stomach), and the host type. Rhabdochona parastromatei Bilqees, 1971, is synonymized with H. stromatei, whereas Heptochona sindica Akram and Pie de Imprenta, 1988, and H. rivdica Akram, 1988, are invalid names. Heptochona varmai is transferred to another genus as Rhabdochona varmai (Gupta and Masoodi, 1990) n. comb. Rhabdochona varmai, Heptochona schmidtii Arya, 1991, and Rhabdochona marina Lakshmi and Sudha, 1999, are considered species inquirendae.
Keywords: nemoci ryb; Tuna; tuňák; Spiruroidea; ostrovy Indického oceánu; Fish Diseases; prevalence; Indian Ocean; Female; Microscopy, Electron, Scanning; zvířata; Indický oceán; Dracunculoidea; infekce hlísticemi řádu Spirurida; ženské pohlaví; Male; mikroskopie elektronová rastrovací; Indian Ocean Islands; Prevalence; Animals; mužské pohlaví; Spirurida Infections